Frequency-Dependent Anisotropic Electromagnetic Responses of Fractured Reservoirs with Various Hydrate Distributions Based on Numerical Simulation - Shengbiao Liu; Gaowei Hu; Qingtao Bu; Yapeng Zhao; Zhiwen Sun (Journal of Marine Science and Engineering, 2024)
Geophysical methods detecting electromagnetic properties (e.g., conductivity, relative permittivity, and dielectric loss factor) have been developed into an important tool to accurately assess the hydrate-bearing reservoirs. The key to the satisfying inversion of the electromagnetic collected data is the precise understanding of the electromagnetic responses in hydrate-bearing reservoirs. However, the frequency-dependent anisotropic electromagnetic responses in fracture-filling hydrate reservoirs remain poorly understood. To acquire the above understanding, we use a numerical simulation method to investigate the frequency-dependent anisotropic conductivities, relative permittivities, and dielectric loss factors of the constructed fracture-filling hydrate digital cores. The fractures in digital cores are aligned along a certain direction and contain the hydrate with various distributions and saturations. The simulated electromagnetic behaviors are comprehensively analyzed and explained by the effects of the electrical polarization, the aligned fractures, as well as the occurrence of hydrate with various distributions and saturation in fractures. The results show that the conductivities enhance while the relative permittivities reduce with increasing frequency, respectively, and their dispersion amplitudes at the frequency scope roughly between 100 MHz and 3000 MHz are more dramatic than that at other frequency ranges. The obtained dielectric loss factors increase first and then decrease with frequency and display peak value at the frequency of approximately 1000 MHz. The conductivities, relative permittivities, and loss factor peak values vertical to the fractures are lower than that in the other direction under the same conditions, respectively. It is found that these three parameters for all hydrate distributions and frequencies reduce with the enhancement of hydrate saturation, whereas the decreasing trends in conductivities and relative permittivities are distinct among the various hydrate distributions. The research results would be possible to pave a way for better identifying and evaluating hydrate resources of fractured reservoirs using the collected electromagnetic data.